SYNTHESIS, SPECTRAL CHARACTERIZATION AND EVALUATION OF INVITRO ANTIBACTERIAL ACTIVITY OF ISONICOTINOYL HYDRAZONES BEARING PYRIDINE MOIETY - B. MOKSHARAGNI,; KANDERI DILEEP KUMAR,; S. CHANDRASEKHAR,; K. HUSSAIN REDDY, (International Journal of Pharma and Bio Sciences, 2015)
Isonicotinoyl and nicotinoyl hydrazones bearing pyridine moiety have been synthesized by simple condensation reaction between carbonyl compounds(1-3) viz. 2-formyl pyridine, 2-acetylpyridine, 2- benzoylpyridine and isonicotinic acid hydrazide (4)/nicotinic acid hydrazide(5). All the hydrazones are thoroughly characterized by IR, 1H- NMR and mass spectral data. Syntheses of these compounds are further confirmed by mass spectrometry. All the compounds (6-11) were screened for their anti-bacterial activities against Staphylococcus aureus, Bacillus subtilis, Escherichia coli and Salmonella typhi . Isonicotinoyl hydrazones show more antibacterial activity than the corresponding nicotinoyl hydrazones. Substituent groups -H, -CH3 and C6H5 groups of azomethine carbon are varied. The hydrazones having a methyl group attached to azomethine carbon atom show more pronounced activity.